PENGARUH LOCUS OF CONTROL, TEKANAN ANGGARAN WAKTU KOMITMEN PROFESIONAL, TERHADAP PERILAKU DISFUNGSIONAL AUDITOR - Ongky Hartanto (EKUITAS (Jurnal Ekonomi dan Keuangan), 2016)
Dysfunctional audit behavior is any action taken in the implementation of the auditor's audit program that can reduce or degrade the quality of the audit directly or indirectly. Researchers wanted to determine the effect Effect of locus of control, time budget pressure, and professional commitment to the dysfunctional behavior of auditors. This research is a quantitative research. In this study, the population is one hundred twenty three Auditor of KAP in Surabaya. Auditor sample are ninety four, which will be drawn at random from a population. The sampling technique used in this research is proportional sampling. Professional Commitment, Locus of Control and time budget pressure influence Dysfunctional AuditorBehavior. Professional Commitment, Locus of Control and time budget pressure significantly influence Dysfunctional Behavior Auditor with significant value less than standard.KAP can conduct training arrangements Locus of Control, control time budget pressure, increased professional commitments in order to suppress the dysfunctional behavior of auditors.